Mineral nutrition of vegetable crop XXX: absorption of micronutrients by four strawberry (Fragaria spp) cultivars - Souza, A. F.; Haag, H. P.; Oliveira, G. D. de; Sarruge, J. R.; Minami, K. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
The aim of this work was to estimate the differences in nutrients uptake and exportation of micronutrients by the fallowings cultivars: Campinas (IAC-2712), Camanducaia (IAC-3530); Monte Alegre (IAC-3113) and SH-2. The experimental was carried out in a soil - Terra Roxa Extruturada type, "Luiz de Queiroz", serie. The experimental design was that randomized blocks with four replications and analysed together following the design of split-plot. The soil of the plots were revolved to a deep of 12 cm. following application of 10 kg. organic matter/m². The fertilizers were applied in the groove and in the same amount for all cultivars: Ammonium sulfate (20% N); triple superpohsphate (20% P2O5); potassium chloride (60% K2O). Thirty days of ter planting, 10 g./plant of ammonium sulfate was applied. After 76 days from planting, the first sample was taken. Other samples were taken in equal intervals of 20 days, up to 216 days. The samples were devided into stems, leaves and fruits. Chemical analysis were sun for B, Cu, Fe, Mn and Zn. The followings conclusions could be drawn. The were differences our micronutrients content in stems and leaves among the cultivares (B, Cu, Fe, Zn) and in the fruits for B, Cu and Fe.